Preparation of silver nanoparticles by gamma Irradiation method using chitosan as stabilizer - Nguyen , Tan Man; Le , Hai; Le , Huu Tu; Tran , Thu Hong; Nguyen , Duy Hang; Pham , Thi Le Ha; Tran , Thi Thuy; Tran , Thi Tam; Nguyen , Trong Hoanh Phong; Le , Xuan Cuong (Nuclear Science and Technology, 2014)
Silver nanoparticles were prepared from (Ag+) aqueous solution by the method of γ-ray irradiation using chitosan as stabilizer. The saturated conversion dose (Ag+ à Ago) determined by UV-Vis spectroscopy was found to be about 16 kGy. The UV-Vis spectrum showed that an absorption peak at λmax = 400 nm due to surface plasma resonance. The image of transmission electron microscopy (TEM) showed that the silver nanoparticles were mostly spherical in shape and the average diameter was of about 12 nm. The prepared colloidal silver nanoparticles solution was in good stability during storage time.